2019
DOI: 10.3389/fimmu.2019.02313
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Anti-inflammatory Action of Neutrophil Extracellular Traps in PAD4-Deficient Mice Contributes to Aggravated Acute Inflammation After Myocardial Infarction

Abstract: Innate immune responses and rapid recruitment of leukocytes, which regulate inflammation and subsequent healing, play a key role in acute myocardial infarction (MI). Peptidylarginine deiminase 4 (PAD4) is critically involved in chromatin decondensation during the release of Neutrophil Extracellular Traps (NETs) by activated neutrophils. Alternatively, activated macrophages (M2) and accurate collagen deposition determine the repair of the infarcted heart. In this study, we investigated the impact of NETs on mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 61 publications
1
55
0
Order By: Relevance
“…The physiological level of ROS plays a key role in cell signal transduction and stabilization of the intracellular environment. Some ROS, especially H 2 O 2 , are considered as local signaling molecules [ 18 ]. Therefore, completely quenching the ROS may interrupt the normal signal cascade and have serious adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological level of ROS plays a key role in cell signal transduction and stabilization of the intracellular environment. Some ROS, especially H 2 O 2 , are considered as local signaling molecules [ 18 ]. Therefore, completely quenching the ROS may interrupt the normal signal cascade and have serious adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Il6 is a well-known inflammation-related gene, and many studies regard it as an indicator of inflammation. 43 , 44 We did not discuss it in depth. Ptgs2, also called COX-2, promotes cell proliferation in tumors, accelerates angiogenesis, 45 and reduces inflammation in myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial role of neutrophils in the conversion of macrophages to a reparative phenotype, as well as the timely development of a fibrotic scar, is evident from studies in mice showing that neutrophil depletion leads to poorer myocardial function and the development of AHF [ 24 ]. Recent data from a murine model of MI indicates that NETs may promote resolution of inflammation [ 25 ] and yet another study showed that NETs likely influence the conversion of monocytes to scar-generating fibrocytes [ 15 ]. Other beneficial effects of neutrophils could mitigate the potential detrimental effects of NETs, complicating interpretation of our results.…”
Section: Discussionmentioning
confidence: 99%